HYDROFRESH (HYDROGEL FRESHENER) PRODUCT MANUFACTURE TRAINING IN KUALA LANGSA VILLAGE - Erni Junaida; Nurlaila Hanum; Nurlina Nurlina (Global Science Society, 2022)
Family Welfare Programme (PKK) Group is a partner on service activities who are given training in the manufacture of Hydrofresh (Hydrogel Freshner). The product is consist of essential oil, water, alcohol 98% and hydrogel. The problem in the implementation of the service is the lack of knowledge of PKK Group of Gampong Kuala Langsa about the manufacture of Hydrofresh products, and the lack of knowledge of the group about entrepreneurship based on digital marketing. To overcome this problem, motivation is carried out to PKK Group of Gampong Kuala Langsa as a partner about how to increase knowledge and skills in the manufacture of Hydrofresh products as an effort to increase additional income and can be used as a home industry business opportunity, can help the village government to increase the income and welfare of the community of Kuala Langsa Village, and Hydrofresh Products can be used as featured products of the village. The method used in service activities is the training method. The result of community service is the creation of a Hydrofresh product (Hydrogel Freshener), and PKK group of Gampong K uala Langsa gains new knowledge regarding materials for making the product and digital marketing systems.